Cassava diseases: ecology and control - Legg, James P. (Informa UK Limited, 2012)
Cassava is an important crop in many parts of the tropics, but it plays a particularly vital role in sustaining food security in sub-Saharan Africa. Diseases are the greatest biotic constraint to cassava production worldwide. Although the diversity of cassava pathogens is greatest in Latin America, the greatest impacts have been reported from Africa. Most significantly, the dual cassava viral pandemics caused by cassava mosaic virus disease (CMD) and cassava brown streak disease (CBSD) have affected many of the major cassavaproducing countries in Africa, causing losses amounting to billions of dollars annually. Control programs have primarily focused on developing than deploying host plant resistance. Good sources of resistance are available for CMD and cassava bacterial blight (CBB), and germplasm improvement work is increasingly being strengthened through the development of molecular markers for marker-assisted breeding and transgenic approaches. Phytosanitary practices, mainly involving the selection of disease-free planting material and quarantine measures to avoid long-distance spread, have been widely used. New disease outbreaks in both Asia (CBB) and Africa (CBSD), however, highlight the need for continued vigilance in efforts to understand the ecology of cassava diseases and develop robust and sustainable management solutions.